Dag Hammarskjöld, the United Nations and the decolonisation of Africa - Melber, Henning 1950- (Oxford scholarship online, 2020)
In 1953 Dag Hammarskjöld became the second Secretary-General of the United Nations-the highest international civil servant. Before his mission was cut short by a 1961 plane crash in then Northern Rhodesia (today Zambia), he used his office to act on the basis of anti-hegemonic values, including solidarity and recognition of otherness. The dubious circumstances of Hammarskjöld's death have received much attention, including a new official investigation (which is summarized in a chapter), but have perhaps overshadowed his diplomatic legacy-one that has often been hotly contested. This text summarizes Hammarskjöld's personal background and the normative frameworks of the United Nations